Patterned transgene expression in multiple channel bridges after spinal cord injury - De Laporte, Laura (2010)
Patterning of gene delivery on sub-millimeter length scales within tissue engineering scaffolds can provide a fundamental technology to recreate the complex architectures of tissues. Surface-mediated delivery of lipoplexes mixed with fibronectin was investigated to pattern vectors within 250 µm channels on poly (lactide-co-glycolide) (PLG) bridges. Initial studies performed in vitro on PLG surfaces indicated that a DNA density of 0.07 µg/mm(2) inside each channel with a weight ratio of DNA to fibronectin of 1:20 maximized the number of transfected cells and the levels of transgene expression. Patterned vectors encoding for nerve growth factor (NGF) resulted in localized neurite extension within the channel. Translation to 3D multiple channel bridges enabled patterned transfection of different vectors throughout the channels for ratios of DNA to fibronectin of 1:4 and multiple DNA depositions, with a large increase of neural cell bodies and neurite extension for delivery of DNA encoding for NGF. In vivo, the immobilization of non-viral vectors within the channels resulted in localized transfection within the pore structure of the bridge immediately around the channels of the bridge containing DNA. This surface immobilization strategy enables patterned gene delivery in vitro and in vivo on lengths scales of hundreds of microns and may find utility in strategies aims at regenerating tissues with complex architectures.